MULTICULTURAL LEADERSHIP: CONCEPT AND IMPLEMENTATION IN EDUCATIONAL INSTITUTIONS - Syaharuddin; Mohamad Iwan Fitriani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Multicultural leadership has become a crucial aspect in addressing the challenges of diversity within educational institutions, making this research significant in providing an in-depth understanding of its implementation. This study aims to explore the concept and application of multicultural leadership within the context of educational institutions. Using a Systematic Literature Review approach, the research analyzes literature indexed in Scopus, DOAJ, and Google Scholar with focusing on publications from 2014 to 2024. The evaluation results indicate that multicultural leadership has a significantly positive impact on student engagement and academic achievement. This approach not only enhances student motivation but also strengthens their ability to collaborate and interact with individuals from diverse cultural backgrounds. Consequently, the implementation of inclusive policies in education becomes increasingly vital for fostering a learning environment that supports diversity and facilitates the optimal development of students' potential. This study contributes to the understanding of the importance of multicultural leadership in improving the quality of education that is inclusive and responsive to the needs of all students.